STRUKTUR DAN FUNGSI SOSIAL CERITA RAKYAT LEGENDA DATUAK PARPATIH NAN SABATANG DI MUNGGU TANAH JORONG BATU PALANO NAGARI SALAYO KECAMATAN KUBUNG KABUPATEN SOLOK - Helmi, Welly; Zulfadhli, Zulfadhli (Universitas Negeri Padang, 2019)
This study aims to describe: (1) the structure of local legend Datuak Parpatih Nan Sabatang’s grave in Munggu Tanah, Jorong Batu Palano, Nagari Salayo, District Kubung, Solok Regency, and (2) the social function of local legend Datuak Parpatih Nan Sabatang’s grave in Munggu Tanah, Jorong Batu Palano, Nagari Salayo, District Kubung, Solok Regency. The source of this research data is story about local legend Datuak Parpatih Nan Sabatang’s grave in Munggu Tanah, Jorong Batu Palano, Nagari Salayo, District Kubung, Solok Regency. There are two stages to collect the data. First, doing interview with informant and record it. Then, transcribe the recordings. Second, collecting data about informant environment. Based on result of the study concluded: (1) The folklore of local legend Datuak Parpatih Nan Sabatang’s grave told by informant with understoodable language, have ten character, the story’s background is in Nagari Salayo, and theme of the story is about Datuak Parpatiah’s body contested, and (2) social function of the local legend Datuak Parpatih Nan Sabatang’s grave are for entertain, education, cultural preservation, and group identity. Keywords: folklore, structure, social function, local legend